An Alternative for Turkish Serials: Uses and Gratifications of Watching Indian Soap Operas by Turkish Female Viewers - Yeliz Yücel; Yeşim Ceren Çapraz (Türkiye İletişim Araştırmaları Dergisi)
In the past few years, the popularity of Indian soap operas has skyrocketed in Turkey, especially in 2016 due to Is Pyaar Ko Kya Naam Doon? (Bir Garip Aşk). The present article investigates female viewers’ motivations for watching Indian soap operas in Turkey. The study was conducted through qualitative research with semi-structured in-depth interviews with 30 female viewers between the ages of 22-60, who were primarily homemakers. This article has revealed five uses and gratifications of Turkish female viewers for watching Indian soaps: Identification, Guilty Pleasure, Relaxation and Escape, Moral Support, and Idealization. Results show that watching Indian soap operas is affected directly by participants’ favorability toward keeping social order (religious, traditional, and familial values) in the right way, their perceived concept of female power, and their willingness to live traditionally. The most unexpected and remarkable finding of this research is the use of watching Indian soaps as a protest against Turkish serials that include sexually explicit content and morally corruptive scenes. Unlike watching Westerner soaps, resistance cannot be found in the uses and gratifications of watching Indian soaps.